Duodenum in the right hemithorax: An unusual case of a large paraesophageal hernia - Mahisha Virdiana; Vijayendra Kedage; Manasa Ubarale; K. Rajgopal Shenoy (International Journal of Abdominal Wall and Hernia Surgery)
Paraesophageal hernia is an uncommon condition where the gastric fundus herniates through the diaphragm without the accompanied migration of the gastroesophageal junction. A woman in her late 60s presented with symptoms of vomiting and decreased appetite for 1 year, accompanied by abdominal fullness in the epigastrium, nausea, and retrosternal burning sensation. Her symptoms worsened over the past month, leading to intolerance to a liquid diet. Upon examination, a vague, tender mass was palpated over the epigastrium, and decreased breath sounds were noted over the right hemithorax. Computed tomography suggested the presence of paraesophageal hernia. An exploratory laparotomy was performed. Intraoperatively, a 4 cm paraesophageal diaphragmatic defect was found through which the antrum and the first part of the duodenum had herniated. The hernial contents were reduced, and anatomical closure was performed. Paraesophageal hernias necessitate careful history and examination, along with an individualized treatment approach, to achieve optimal patient outcomes.